(untitled) (Świat Idei i Polityki, 2013)
An alien is a person who does not have Polish citizenship. If you stayed on Polish territory, is protected by law, just as a Polish citizen. On 1 May 2004, Poland has become a European Union member states. Polish border on the Bug became the eastern border of the European Communities, and in a broader geographical and geopolitical plan a whole continent, our country occupies a central position. It is therefore likely that Poland has a much greater extent start to act as a transit country in Europe. Poles are aware of the opportunities and threats arising from this situation. On one hand, is expected to shift to the Polish foreign investment from the present EU countries, on the other hand, the forecasts point to a phenomenon of increasing number of Polish immigrants. Assuming a responsible role, related to personal and goods at the border, Poland is open to visitors from around the world. The hospitality we are proud of the Poles, is reflected in the rules governing residence of foreign nationals on Polish territory. They allow you to cross the border every foreigner, regardless of origin, religion, social or political views.